Practices, needs and beliefs of lower secondary science teachers in Trinidad and Tobago: A research report - George, June M. (The University of the West Indies, 1995)
This project represents and initial attempt at understanding the science education scenario in Trinidad and Tobago. It focuses on the part of the system where there is most diversity—the lower secondary sector—and targets one group of stakeholders—the teachers of science. The study proposed nine research questions that aimed to elicit the following: 1) background and qualifications of the teachers, 2) their views of the nature of science and their role as teachers of science at this level, 3) their views of the nature of technology and its role in the secondary school curriculum, 4) their conceptions of the process approach to the teaching of science and the extent to which they incorporate it in their science classes, 5) their perception of the role of practical work in the teaching of science at this level and the strategies used to incorporate practical work in their teaching, 6) their views of current offerings in science at this level, 7) their views of the adequacy of the various types of resources available for teaching science at this level, 8) their perception of the aids/obstacles to science teaching at this level, and 9) their perception of their greatest strengths and needs. Questionnaires were sent to 82 government and government-assisted schools with a lower secondary sector. Completed questionnaires were received from 254 teachers in 73 of the schools targeted. This report presents the findings of the statistical analysis of the responses to each of the research questions. Recommendations are made for future research work and other action in some of the key areas identified.
Keywords: science teachers